2022
DOI: 10.3390/ijms23137095
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shift Assay for Small GTPase Stability Screening: Evaluation and Suitability

Abstract: Thermal unfolding methods are commonly used as a predictive technique by tracking the protein’s physical properties. Inherent protein thermal stability and unfolding profiles of biotherapeutics can help to screen or study potential drugs and to find stabilizing or destabilizing conditions. Differential scanning calorimetry (DSC) is a ‘Gold Standard’ for thermal stability assays (TSA), but there are also a multitude of other methodologies, such as differential scanning fluorimetry (DSF). The use of an external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
3
19
2
Order By: Relevance
“…The observed ΔT m in the absence and presence of MgCl 2 (1 mM) was 9.1 °C, which is similar to the ΔT m observed in the protein-probe assay (10.9 °C). 26 We 26 and others 34,35 previously demonstrated that protein concentration can significantly impact not only protein detectability but also the observed T m values. Thus, we determined T m values of HRAS and NRAS at concentrations of 100, 250, and 500 nM in the one-step peptide-probe protocol; T m values were slightly different and protein concentration-dependent (Figure S30).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The observed ΔT m in the absence and presence of MgCl 2 (1 mM) was 9.1 °C, which is similar to the ΔT m observed in the protein-probe assay (10.9 °C). 26 We 26 and others 34,35 previously demonstrated that protein concentration can significantly impact not only protein detectability but also the observed T m values. Thus, we determined T m values of HRAS and NRAS at concentrations of 100, 250, and 500 nM in the one-step peptide-probe protocol; T m values were slightly different and protein concentration-dependent (Figure S30).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The observed T m values and ΔT m (2.9 °C) were slightly higher than those in the 96-well plate protocol, possibly due to differences in assay buffers, plates, volumes, proteins, and AZA concentrations (Table S1). 15,26,34,35 Next, we selected RAS as a target protein to further study the one-step peptide-probe thermal protocol. We first mimicked the PLI-type stabilization of KRAS (500 nM) in both the absence and presence of MgCl 2 (1 mM) (Figure 3A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the methodological articles, Kopra et al [ 3 ] described a new methodology to evaluate and characterize newly designed drug candidates. The authors designed a protocol improving previously established methodologies, of which the sensitivity enables effective studies with non-covalent and covalent drugs at the nanomolar level.…”
mentioning
confidence: 99%